Factores asociados a los trastornos del sueño de pacientes en hemodiálisis en el Hospital Regional de Loreto en el 2021 - Chavez Rocca, Giovanni Michell (2022)
Background: Sleep disorders are a disturbance of the normal sleep cycle that is the associated with the multiple factors: changes in lifestyle and the circadian cycle, comorbidities (COPD, CKD), etc. Objective: The present research aimed to identify the factors associated with sleep disorders in hemodialysis patients at the Regional Hospital of Loreto in 2021. Materials and Methods: An descriptive, cross-sectional study was carried out, where all patients who met the Inclusion criteria were included and the Pittsburg Questionnaire, the Epworth Sleepiness Scale and the Berlin Questionnaire, where sociodemographic, clinical and laboratory variables were associated. Results: A total of 88 patients participated in the study, 50% men and 50% women, 42% of patients were older than 60 years and 51,1% were single. 62%of patients have a normal weight, 47.73% have a Hemoglobin <10.5gr/dL, 37,5% of patients have a stay of 2 to years in Hemodialysis, 88% of patients suffered from Arterial Hypertension. Poor Sleep Quality is determined in 76.1% of patients, which found a significant association with age (p<0,020), low hemoglobin levels (p<0,000), previous medication (0,040) and Obstructive Uropathy (p<0,001). Excessive daytime sleepiness was determined in 78,4% of patients, which found a significant association with age (p<0,006), marital status (p<0,002), low hemoglobin levels (p<0,000) and Hypertension Arterial (p<0,019). A high risk of OSAHS was determined in 45,5% of the patients, where a significant association was found with low levels of Hemoglobin (p<0,003) and Arterial Hypertension (p<0,042) Conclusion: Different factors (age, hemoglobin, previous medication, obstructive Uropathy) are associated with poor sleep quality; excessive daytime sleepiness is associated with age, marital status, hemoglobin and arterial hypertension; and the risk of OSAHS is associated with hemoglobin and arterial hypertension